Perkutánní fenestrace pri postizení lupavým prstem - Pavlicný, R (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2010)
PURPOSE OF THE STUDY: To evaluate, in a retrospective study, the surgical outcomes of percutaneous A1 pulley release in the treatment of trigger digits. MATERIAL: The group evaluated comprised 100 digits in 88 patients. There were 65 women and 23 men. Ten patients had surgery on two digits and one patient on three digits. The patients' average age at the time of surgery was 57.9 years. This procedure was performed on 55 thumbs and 45 fingers (4 index fingers, 19 middle fingers, 19 ring fingers, and 3 little fingers). METHODS: A bent hypodermic needle is used to release the A1 pulley, whose localization is determined as suggested by Froimson. The procedure is performed under local anaesthesia without tourniquet use. Pulley release is done with the needle tip. The finger/thumb is kept in hyperextension of the metacarpophalangeal joint to avoid injury to the nerve and vascular plexus. The extent of tendon release is checked by active motion of the treated digit that should move freely without snapping or locking. Subsequently, a compression bandage is applied for two days, with the digit being exercised immediately after surgery. RESULTS: Of the 100 digits treated, 95 procedures led to complete relief of symptoms and restoration of a full range of motion. Five digits underwent repeat surgery (three percutaneous and two open release procedures). No complaints were reported for 79.7 % and 91.1 % of the treated digits at 2 weeks and 2 months after surgery, respectively. Better results were recorded for the treatment of thumbs. Complications included early trigger finger recurrence in two cases, late recurrence was not recorded. A restricted range of motion after surgery required repeat surgery in three cases. No serious complications such as injury to the tendon, bowstring effect, nerve damage or wound infection were recorded. DISCUSSION: The results of surgery, both percutaneous and open release, in our patient group are comparable with those reported in the literature. In contrast to some authors, we carry out release on all digits. If indicated, we perform percutaneous release also at reoperations. CONCLUSIONS: Percutaneous release has been adopted as a standard method at our department. Because of its minimal invasiveness, it reduces the risk of complications associated with open procedures. It can be carried out at an outpatient department, is less painful and allows the patient to return to daily activities and work in a shorter time.
Keywords: recidiva; Orthopedic Procedures; Recurrence; Female; Postoperative Complications; Trigger Finger Disorder; pooperační komplikace; ortopedické výkony; ženské pohlaví; Humans; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; lupavý prst; miniinvazivní chirurgické výkony; Minimally Invasive Surgical Procedures